“I CAN TELL SHE LOVES ME”: STORY OF A PEER SUPPORT RELATIONSHIP - Bernard, Pauline; Williamson, Bridgett; Wexler, Thomas; Smith, Shannon; Bromage, Billy (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2021)
Peer support has proven its unique role and efficacy in the recovery process of people with mental health and substance use challenges. This narrative explores elements of a peer support relationship, through the eyes of both someone receiving and someone providing that support, within the context of community-based mental health interventions inspired by the citizenship framework of care. The interviewees highlight the personal impacts of the relationship on each person in the dyad and provide a discrete example of the potentiality of peer support work that is practiced outside of the formal mental health system and embedded in the community.